2021
DOI: 10.2196/23432
|View full text |Cite
|
Sign up to set email alerts
|

A Mental Health–Informed Physical Activity Intervention for First Responders and Their Partners Delivered Using Facebook: Mixed Methods Pilot Study

Abstract: Background First responders (eg, police, firefighters, and paramedics) are at high risk of experiencing poor mental health. Physical activity interventions can help reduce symptoms and improve mental health in this group. More research is needed to evaluate accessible, low-cost methods of delivering programs. Social media may be a potential platform for delivering group-based physical activity interventions. Objective This study aims to examine the feas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 72 publications
1
22
0
Order By: Relevance
“…The study is reported in line with the CONSORT 2010 checklist extension for stepped wedge cluster randomised trials (32). The study protocol has been published elsewhere (33) and was informed by pilot work (34).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The study is reported in line with the CONSORT 2010 checklist extension for stepped wedge cluster randomised trials (32). The study protocol has been published elsewhere (33) and was informed by pilot work (34).…”
Section: Methodsmentioning
confidence: 99%
“…showed that a sample size of n=80 would be sufficient to achieve power of 80% with the P value set at 0.05 (34).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations